Should You Meet the Parents? The Impact of Information on Non-Test Score Attributes on School Choice - Elisa Facchetti; Lorenzo Neri; Marco Ovidi (Center for Economic Studies and ifo Institute (CESifo), 2024)
Understanding parental response to non-test score attributes is crucial to design effective school choice systems. We study an intervention providing hard-to-find information on the school environment at local institutions, while holding information on school performance constant. Outflow to private education is reduced by 17%, with larger responses among advantaged students. Parents respond by increasing take-up of offers from local schools, intensifying competition for seats. Social interactions increase the program's impact by 40%. Consistent with our interpretation, the intervention does not affect parental demand for school performance. We conclude that simple, low-cost interventions can improve state schools' finances and peer quality.
Keywords: I24; I28; H75; 330; school choice; non-test score school attributes; information intervention